Molecular regulation of CRAC channels and their role in lymphocyte function - Shaw, Patrick J. (2012)
Calcium (Ca(2+)) influx is required for the activation and function of all cells in the immune system. It is mediated mainly by store-operated Ca(2+) entry (SOCE) through Ca(2+) release-activated Ca(2+) (CRAC) channels located in the plasma membrane. CRAC channels are composed of ORAI proteins that form the channel pore and are activated by stromal interaction molecules (STIM) 1 and 2. Located in the membrane of the endoplasmic reticulum, STIM1 and STIM2 have the dual function of sensing the intraluminal Ca(2+) concentration in the ER and to activate CRAC channels. A decrease in the ER's Ca(2+) concentration induces STIM multimerization and translocation into puncta close to the plasma membrane where they bind to and activate ORAI channels. Since the identification of ORAI and STIM genes as the principal mediators of CRAC channel function, substantial advances have been achieved in understanding the molecular regulation and physiological role of CRAC channels in cells of the immune system and other organs. In this review, we discuss the mechanisms that regulate CRAC channel function and SOCE, the role of recently identified proteins and mechanisms that modulate the activation of ORAI/STIM proteins and the consequences of CRAC channel dysregulation for lymphocyte function and immunity.